Human and financial resource needs for universal access to WHO-PEN interventions for diabetes and hypertension care in Eswatini: results from a time-and-motion and bottom-up costing study - Harsh Vivek Harkare; Brianna Osetinsky; Ntombifuthi Ginindza; Bongekile Thobekile Cindzi; Nomfundo Mncina; Babatunde Akomolafe; Lisa-Rufaro Marowa; Nyasatu Ntshalintshali; Fabrizio Tediosi (BMC, 2024)
Abstract Background Eswatini faces persistent challenges in providing care for diabetes and hypertension, exacerbated by a shortage of healthcare workers. The implementation of WHO-PEN interventions aimed to address these issues, yet their effects on healthcare worker time requirements and associated costs remain unclear. Methods This study employed a time-and-motion analysis and a bottom-up cost assessment to quantify the human and financial resources required for scaling up WHO-PEN interventions nationally in Eswatini for all estimated diabetic and hypertensive patients. Results Findings reveal that healthcare workers in intervention-arm clinics reported longer workday durations compared to those in control-arm clinics, yet spent less time per patient while seeing more patients. The implementation of WHO-PEN interventions increased the workload on healthcare workers but also led to a notable increase in patient care utilization. Furthermore, a morning peak in patient visits was identified, suggesting potential opportunities for optimizing patient flow. Notably, scaling up care provision nationally with WHO-PEN interventions proved to be more cost saving than expanding standard-of-care treatment. Conclusion WHO-PEN interventions hold promise in improving access to diabetes and hypertension care in Eswatini while offering an efficient solution. However, addressing challenges in healthcare workforce creation and retention is crucial for sustained effectiveness. Policy makers must consider all aspects of the WHO-PEN intervention for informed decision-making. Trial registration US Clinical Trials Registry. NCT04183413. Trial registration date: December 3, 2019. https://ichgcp.net/clinical-trials-registry/NCT04183413